Sentinel lymph node positivity in patients undergoing mastectomies for ductal carcinoma in situ (DCIS). - Price, Alison; Schnabel, Freya; Chun, Jennifer; Kaplowitz, Elianna; Goodgal, Jenny; Guth, Amber; Axelrod, Deborah; Shapiro, Richard; Mema, Eralda; Moy, Linda; Darvishian, Farbod; Roses, Daniel (Breast Journal, 2020)
Current guidelines recommend sentinel lymph node biopsy (SLNB) for patients undergoing mastectomy for a preoperative diagnosis of ductal carcinoma in situ (DCIS). We examined the factors associated with sentinel lymph node positivity for patients undergoing mastectomy for a diagnosis of DCIS on preoperative core biopsy (PCB). The Institutional Breast Cancer Database was queried for patients with PCB demonstrating pure DCIS followed by mastectomy and SLNB from 2010 to 2018. Patients were divided according to final pathology (DCIS or invasive cancer). Clinico‐pathologic variables were analyzed using Pearson's chi‐squared, Wilcoxon Rank‐Sum and logistic regression. Of 3145 patients, 168(5%) had pure DCIS on PCB and underwent mastectomy with SLNB. On final mastectomy pathology, 120(71%) patients had DCIS with 0 positive sentinel lymph nodes (PSLNs) and 48(29%) patients had invasive carcinoma with 5(10%) cases of ≥1 PSLNs. Factors positively associated with upstaging to invasive cancer in univariate analysis included age (P =.0289), palpability (P <.0001), extent of disease on imaging (P =.0121), mass on preoperative imaging (P =.0003), multifocality (P =.0231) and multicentricity (P =.0395). In multivariate analysis, palpability (P =.0080), extent of disease on imaging (P =.0074) and mass on preoperative imaging (P =.0245) remained significant (Table 2). In a subset of patients undergoing mastectomy for DCIS with limited disease on preoperative evaluation, SLNB may be omitted as the risk of upstaging is low. However, patients who present with clinical findings of palpability, large extent of disease on imaging and mass on preoperative imaging have a meaningful risk of upstaging to invasive cancer, and SLNB remains important for management.